2009
DOI: 10.2466/pr0.105.2.554-568
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Risk and Personality Traits in Physically and/or Sexually Abused Acute Psychiatric Inpatients: A Preliminary Study

Abstract: The aim of the present study was to analyze hopelessness and the affective temperament profile and MMPI characteristics among suicidal and nonsuicidal psychiatric inpatients with or without childhood physical and sexual abuse. The participants were 62 acute psychiatric inpatients (14 men, 48 women) admitted to the Sant'Andrea Hospital's psychiatric ward in Rome. Participants were administered the Italian versions of the Childhood Trauma Questionnaire, the Mini-International Neuropsychiatric Interview (MINI), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
2
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 44 publications
0
17
2
1
Order By: Relevance
“…The research supports the assertion that, traumatic experience affects the pathway to completed suicide with differing profiles for those who engage in superficial self-harm, near-lethal self-harm, repeated attempted suicide or those who do not engage in these behaviours prior to their death. The data identified only two DSH behaviours linked with trauma experience: repeated suicide attempts were linked with the experience of direct trauma; and Unlike previous studies (Marzano, et al, 2010;Pompili et al, 2009) the likelihood of engaging in near-lethal self-harm was not found to be related to history of trauma. Indeed, those with experience of direct trauma were less likely to engage in SSH prior to completed suicide.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…The research supports the assertion that, traumatic experience affects the pathway to completed suicide with differing profiles for those who engage in superficial self-harm, near-lethal self-harm, repeated attempted suicide or those who do not engage in these behaviours prior to their death. The data identified only two DSH behaviours linked with trauma experience: repeated suicide attempts were linked with the experience of direct trauma; and Unlike previous studies (Marzano, et al, 2010;Pompili et al, 2009) the likelihood of engaging in near-lethal self-harm was not found to be related to history of trauma. Indeed, those with experience of direct trauma were less likely to engage in SSH prior to completed suicide.…”
Section: Discussioncontrasting
confidence: 75%
“…Indeed, it could be argued that the disproportionate level trauma experience, compared with males, may go some way in explaining the heightened risk in female offenders of enacting suicidal behaviour (Pompili et al, 2009) or near lethal self-harm (Marzano, Hawton, Rivlin & Fazel, 2011). However the relationship is complex within a high-risk female offender population, where trauma exposure and deliberate self-harm is very high, but completed suicide is comparatively low.…”
Section: Introductionmentioning
confidence: 99%
“…Pompili et al reported that psychiatric inpatients with a history of childhood abuse showed a higher incidence of the irritable temperament trait than did the non-abused patients (Pompili et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Traumatic events, especially in early life, have been causally linked to schizophrenia (Read, et al, 2005; Gil, et al, 2009). However, it has not been recognized as a risk factor for suicide in this group, although it has been viewed as a risk factor in the general population (Dube, et al, 2001; Afifi, et al, 2008; Pompili, et al, 2009). Interestingly, we found higher rates of early physical and sexual abuse among persons with prior suicide attempts.…”
Section: Discussionmentioning
confidence: 99%